Compilation of test questions for checking the level of students’ knowledge of drawing geometry - Kusebaev Уалихан (Рroblems of engineering and professional education, 2023)
The article deals with checking the level of students’ knowledge o f descriptive geometry. As the main method of control of knowledge offered testing. An example of preparation of test questions on descriptive geometry.